THE EFFECT OF FEEDING CHEESE WHEY ON LANDRACE CROSSBRED PIG PERFORMANCE AGED 8-20 WEEKS - W. D., Hartadi; Budaarsa, K.; Mahardika, I G. (Jurnal Peternakan Tropika; Vol 7 No 3 (2019): Issue 7 No. 3 - 2019; September - December 2019DO - 10.24843/ejpt.2019.v07.i03.p011, 2019)
This study aims to determine the effect of feeding cheese whey on the performance of landrace crossbred pig aged 8-20 weeks.The research was conducted for 12 weeks in a pigpen owned by Mr. I Ketut Muliada located in Mengwi, Badung. The design used was a Completely Randomized Design consisting of four treatments, namely: A (ration without addition of cheese whey) as a control, B (ration and addition of 0.5 liters cheese whey/pig), C (ration and addition of 1 liters cheese whey/pig) and D (ration and addition of 1.5 liters of cheese whey/pig). Each treatment consisted of four replications with an average initial body weight of 14.95 ± 3.14 kg. Variables observed were body weight gain, ration consumption, Feed Conversion Ratio and the cost of feed per kg body weight. The results showed that the provision of cheese whey as additional feed had significant effects (P<0,05)on body weight gain and FCR, but had no significant effects(P>0,05) on ration consumption and cost of ration per kg body weight. Based on the results of the study it was concluded that the administration of cheese whey as addition feed has no effect on feed consumption but increased body weight gain and decreased the FCR of landrace crossbred pig aged 8-20 weeks. Keywords: landrace crossbred pig, cheese whey, performance